Penerapan Model Pembela Jaran Van Hiele Untuk Meningkatkan Hasil Belajar Siswa Pada Siswa Kelas V - ., Nurul Laili; ., Ludfi Arya Wardana; ., Didit Yulian Kasdriyanto (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The lack of educator skills in choosing learning models will have a negative impact on their students. The existence of the problem of low student learning outcomes and student activity made the researchers take the initiative to conduct oriented research to improve mathematics learning outcomes using the van hiele learning model. The subjects of this study were 32 grade 5 students. The research location is at SDN Pondok Kelor 1 Paiton Probolinggo. In its implementation using Classroom Action Research (CAR). The data collection process was carried out by observation, interviews, documentation, and learning achievement tests. The data analysis process utilizes a qualitative descriptive type. This qualitative descriptive describes the quality or the quality of the results of the implementation carried out. The results obtained from research on the use of the Van Hiele learning model resulted in an increase in student learning outcomes. Evidenced by the acquisition in the first cycle the value of student learning activities with good criteria, namely 45.86%, in the second cycle increased to 78.11%. In addition, student learning outcomes when calculated using the average score have increased, from 57 in cycle I to 74 in cycle II.